The Effect of Different Reserve Requirement Ratio Applications Based on Maturity on TL Deposits (Third Sector Social Economic Review, 2025)
The aim of this study is to investigate the impact of the Central Bank of Türkiye's differentiated reserve requirement policy on TL deposit groups. Since no empirical study has been conducted on this topic, it is expected to make a significant contribution to the literature. An empirical analysis is employed using monthly data for the period 2011:9-2025:6 to analyze how relative reserve requirement ratios affect the share of deposits with different maturity structures. Fourier unit root tests and Fourier ADL cointegration test, which consider structural breaks, have been used. In addition, FMOLS estimator and error correction model have been employed to estimate the short- and long-term relationships between variables. The Fourier ADL cointegration test results indicate the existence of a significant long-term relationship between reserve requirement ratios and TL deposit groups longer than 3 months. The FMOLS estimator and the error correction model also confirm the Fourier ADL cointegration findings. On the other hand, there is no significant relationship between TL deposit types with maturities of 3 months or less and the reserve requirement ratio. These findings suggest that the significant differentiation of reserve requirement ratios for TL deposit groups with maturities longer than 3 months is a contributing factor. Furthermore, it is believed that assigning many objectives to reserve requirements and inconsistency between goals may also lead to this result. Therefore, it would be beneficial for the central bank to simplify its reserve requirement policies.
Keywords: Monetary policy; financial stability; reserve requirement ratio; maturity of TL deposits; Fourier structural break